Characteristics of Egg Yolk Powder Added Carrot Puree (Daucus Carota L.) and Isolated Soy Protein - Wulandari, Zakiah; Imawan, Salsabila Ma’shum; Suryati, Tuti (Universitas Halu Oleo, 2023)
Egg powder is widely used in various industries, but the fat content in the egg yolks makes egg yolks powder more easily rancid due to oxidation. One way to inhibit the oxidation reaction of compounds is by adding antioxidants such as carrots. This research aims to evaluate the physicochemical properties, organoleptic properties, and antioxidant activity of egg yolk powder with the addition of carrot puree and isolated soy protein (ISP). The experimental design used in this study was a randomized block design (RBD) based on the manufacturing period, there were three groups of manufacturing periods. The results showed that adding carrot puree and ISP resulted in higher crude protein content and fiber content of egg yolk powder with the color and texture quality criteria preferred by the panelists. The addition of carrot puree and ISP did not affect the water content, pH, aw, and crude fat content. The addition of carrot puree in lower antioxidant activity than the control. Egg yolk powder with the addition of 15% carrot puree and 10% ISP gave the best results for the analysis of physicochemical properties, organoleptic properties, and antioxidant activity. Keywords: antioxidant activity, carrot puree, egg yolk powder, organoleptic property, physicochemical property